Design and Development of a Web-Based Cashier and Accounting System Using CodeIgniter 4 - Nur Wildayani Kahar; Abdul Malik; M. Hasanuddin; Muh. Hajar Harike; Suharsono Bantun (Program Studi Teknik Komputer, 2024)
In the digital era, traditional manual bookkeeping and cashiering systems are no longer effective for managing store operations. CV Sinar Situju faces a particular problem in data management that is inefficient and error-prone. The solution offered is the development of a web-based bookkeeping and cashier system using the CodeIgniter 4 framework with the Rapid Application Development (RAD) method. This research method includes needs analysis, system design, implementation, and testing. The test results show that the system has good response speed, high stability, and is able to handle high user loads. The system improves operational efficiency, transaction recording accuracy, and data security. This research recommends the implementation of a web-based system to improve operational performance and customer satisfaction.